2020
DOI: 10.1186/s12904-020-00684-0
|View full text |Cite
|
Sign up to set email alerts
|

Professional oral care in end-of-life patients with advanced cancers in a hospice ward: improvement of oral conditions

Abstract: Background In end-of-life patients with advanced cancers, oral examination, oral care, and oral re-examination are crucial. Although oral symptoms are among the major complaints of end-of-life patients, few studies have focused on oral care in these patients. In this study, the association between oral symptoms and oral dryness among end-of-life patients was examined, and improvement of oral conditions after oral care interventions by a professional dentist was quantified. Methods This prospective interventio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…On the other hand, fungal amount is related with oral moisture condition and oral health. Wu et al reported that oral care intervention in patients with end stage of cancer reduced detection of Candida on the tongue, accompanied by a decrease in OHAT score [56], which was confirmed by the present results. OHAT criteria for assessments of lip, tongue, gum tissues, and saliva include dryness, with oral dryness one of the significant factors related to fungal colonization in the oral cavity [57,58].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, fungal amount is related with oral moisture condition and oral health. Wu et al reported that oral care intervention in patients with end stage of cancer reduced detection of Candida on the tongue, accompanied by a decrease in OHAT score [56], which was confirmed by the present results. OHAT criteria for assessments of lip, tongue, gum tissues, and saliva include dryness, with oral dryness one of the significant factors related to fungal colonization in the oral cavity [57,58].…”
Section: Discussionsupporting
confidence: 89%
“…A sponge brush, a toothbrush, an oral care gauze, an aspirator with a suction tube, and water or a gel-like oral moisturizer (hereinafter referred to as gel) were used. Oral care was performed in a series of steps, as follows [24]: (1) the oral cavity was moisturized with an oral moisturizer and sponge brush; (2) pseudo-plaque was removed with a toothbrush; (3) dry sputum was collected with a sponge brush. This procedure was repeated to remove the pseudo-plaque.…”
Section: Study Protocolmentioning
confidence: 99%
“…Effective intervention to prevent and control oral problems is necessary for long-term care facilities. 56 Uncontrolled oral problems contribute to worsening quality of life (QOL), particularly among the most vulnerable population, which is close to the end of their life. According to the Fédération Dentaire Internationale (FDI) World Dental Federation, a new concept of oral health has been adopted as "multifaceted and includes the ability to speak, smile, smell, state, touch, chew, swallow, and convey a range of emotions through facial expressions with confidence and without pain, discomfort, and disease of the craniofacial complex.…”
Section: Discussionmentioning
confidence: 99%